Fibrinogen and prothrombin blood content under ischemic stroke complicated by type 2 diabetes mellitus - Kravchenko, Olha; Tymoshenko, Maria; Tsarenko, Tetyana (ScienceRise: Biological Science, 2017)
The article is dedicated to evaluation of general clinical and some hemostatic parameters (fibrinogen, soluble fibrin monomeric complexes and prothrombin content) of patients with ischemic stroke under presence or absence of type2 diabetes mellitus. It has been established that diabetes mellitus patients with ischemic stroke are more likely to have hyperlipidemia, peripheral vascular disease and high body mass index. The conducted research has established the statistically significant changes of fibrinogen and soluble fibrin monomer complexes (SFMC) levels under both investigated pathologies (ischemic stroke and ischemic stroke complicated by insulin-independent diabetes mellitus). SFMC, the early marker of thrombophilia, was significantly higher compared to the reference values in case of stroke as well as stroke with diabetes. It was established that fibrinogen indexes were higher under IS with DM, whereas SFMC had more deviated meanings comparing with the control parameters under ischemic stroke alone. The higher SFMC level in acute phase of stroke independently of diabetes present was a statistically confirmed predictor of mortality. Nevertheless statistically significant differences of fibrinogen and SFMC levels in patients with ischemic stroke and IS+DMwere not detected and there were no differences of protrombin content neither comparing with the control nor between the studied pathologies. The obtained results have shown that ischemic stroke with and without type 2 diabetes mellitus are characterized by similar changes of the investigated hemostasis parameters